Use of Space for Work at Home in the Indonesian Household Context - Della Ayu Siti Fathimah; Joko Adianto; Rossa Turpuk Gabe (International Journal of Built Environment and Scientific Research, 2023)
This paper explores how roles and values in Indonesian households are taken into consideration when determining the use of space to work at home. Along with socioeconomic and technological developments, working at home is increasingly becoming a common thing to find in Indonesia. Work activities must be carried out in accordance with the context of the household that has established its own conventions, roles, meanings, and values. However, taking the role and value factors of the household into consideration when exploring the reasons behind the spatial utilization for work at home still receives minimal attention. Using a qualitative research approach, this study explores which aspects of roles and values within the household are taken into consideration in determining how the space available at home is used for work. This study also answers the types of spatial utilization formed as the result of the aforementioned roles and values. The consideration factors found are different for each type of household so that the resulting form of space use is also different. The findings from this study found that consideration of certain household aspects can also give rise to its own form of spatial use.